Unusual details of everyday life from the notary registry of Petrus, called Perençanus, a notary from Zadar (1365-1392) - Bartulović, Anita (Array, 2019)
Most of the contracts from the unpublished notary registry of the notary Petrus from Zadar, known as Perençanus (1365–1392) provide only the most basic information about the contractors, the type of legal business and its subject matter, witnesses, officials, etc. because of their usual formulaic nature. In this paper, we shall deal with contracts that break this uniformity common to medieval notary records by presenting unusual and interesting details of people’s lives, largely found in the formulae contrahentes, res and causa. The content of these contracts is analyzed at two levels: within the context of studying the medieval mentality and within the linguistic context.